Strategi Terhadap Pengembangan Kelembagaan BUMDESA di Kabupaten Jember - Herman Cahyo Diartho (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2017)
This study aims to determine the institutional performance of BUMDESA in Jember District. This research uses explanatory method. Data and information required consist of primary data that is data obtained from questionnaire or interview and secondary data that is supporting data obtained from related institution. The unit of analysis is Institutional BUMDesa in Jember District. The results of this study indicate that (1). Institutional governance is a key determinant of business success of each type of BUMDesa. This is because each type of business BUMDesa not stand alone but has a linkage chain with other factors that greatly affect the sustainability of the business. This linkage is like a link and when this chain breaks up the effort undertaken by BUMDesa will be affected, (2). The sustainability of BUMDesa is strongly influenced by the scale and business scope. BUMDes that run internal business (serving the needs of local people (such as basic needs, tractor rental) with local reach and scale, are generally at low risk so as to be healthy and sustainable, of course that the BUMDesa is managed with sufficient managerial capacity and (3) The growing community of social solidarity and local wisdom is much stronger and more sustainable than the BUMDES that were born because of government intervention from above because local wisdom parallel with the wealth of social capital and political capital is a very influential factor durability and sustainability of BUMDesa.